2013
DOI: 10.1111/nure.12028
|View full text |Cite
|
Sign up to set email alerts
|

Meat, fish, and esophageal cancer risk: a systematic review and dose-response meta-analysis

Abstract: Risk factors for esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC) are well defined, while the role of diet in these conditions remains controversial. To help elucidate the role of particular dietary components, major bibliographic databases were searched for published studies (1990-2011) on associations between esophageal cancer risk (EC) and consumption of various types of meat and fish. Random-effects models and dose-response meta-analyses were used to pool study results. Subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 69 publications
2
64
2
3
Order By: Relevance
“…In developing and less developed countries, the death rate from cancer will be higher due to weak economic conditions, greater tobacco use, poor diet, greater alcohol consumption, higher incidence of other cancers and, most importantly, lack of adequate access to diagnostic and treatment facilities (Liu et al, 2014;Mao et al, 2011;Rezaianzadeh et al, 2016;Rezaianzadeh et al, 2017). Conversely, incidence of some cancers, such as EC, was reduced in developed countries due to better treatment methods, better lifestyle screening, lower risk of infectious diseases, and better access to health care services (Lin et al, 2013;Mai et al, 2014;Salehi et al, 2013;Spechler, 2013). Moreover, in countries with better economic and social conditions, and particularly access to earlier diagnosis of diseases, the survival rate of patients will presumably be greater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing and less developed countries, the death rate from cancer will be higher due to weak economic conditions, greater tobacco use, poor diet, greater alcohol consumption, higher incidence of other cancers and, most importantly, lack of adequate access to diagnostic and treatment facilities (Liu et al, 2014;Mao et al, 2011;Rezaianzadeh et al, 2016;Rezaianzadeh et al, 2017). Conversely, incidence of some cancers, such as EC, was reduced in developed countries due to better treatment methods, better lifestyle screening, lower risk of infectious diseases, and better access to health care services (Lin et al, 2013;Mai et al, 2014;Salehi et al, 2013;Spechler, 2013). Moreover, in countries with better economic and social conditions, and particularly access to earlier diagnosis of diseases, the survival rate of patients will presumably be greater.…”
Section: Discussionmentioning
confidence: 99%
“…EC is one of the cancers that are strongly associated with social and economic status (Dar et al, 2013;Wang et al, 2015). Studies have shown that tobacco, weak nutrition and alcohol are most associated with EC, especially the SCC type (Lin et al, 2013;Liu et al, 2014;Salehi et al, 2013). Furthermore, low income populations have a higher chance of mortality from EC because they have less access to prevention and treatment services (Wang et al, 2013;Wei et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another four meta-analyses confirmed an increased risk of both squamous and adenocarcinoma with higher red and/or processed meat intake, 19,20,23,25 however, there is evidence for heterogeneity by the cancer subtype. 21 For pancreatic cancer, red meat intake indicated a nonsignificantly increased risk, while for processed meat the association was significant (table I). This was confirmed in a meta-analysis based on eleven prospective studies.…”
Section: Artículo Especialmentioning
confidence: 99%
“…19 A recent literature review reported that processed meat was significantly associated with esophageal adenocarcinoma, but not with ESCC. 20 Although a number of epidemiologic studies have focused on the association between processed meat and EC, there is a limited number of studies that specified the association between salted meat and ESCC. 21,22 Yanting County, located in the Southwest China, is among the several high ESCC risk areas in the country.…”
mentioning
confidence: 99%